Determination of possibilities of the use of high-intensive trainings facilities on lessons health aerobics - N.A. Bryukhanova; O.V. Bulgakova; T.I. Mokrova; Y.A. Bogashchenko (Physical Education of Students)
The purpose of experiment was an exposure of reaction of heart rate of students on the increase of rate of musical accompaniment. 89 students of the first course took part in experimental employments. Height of step platform 15-20 centimetre. The large reaction of heart rate is exposed considerably on the increase of height of step platform (on 18,3 %), what at growth of music rate (on 8,5 %). Also appeared, that 14 from 89 students have weak functional preparedness: already at the rate of music of 138-142 shots in a minute and height of step platform 15 centimetre, heart rate for them attained an age-dependent maximum (on the average 207 shots in a minute). It is recommended to utillize in employments the increase of intensity only in the limited volume: increase of music rate to 142-45 shots in a minute or heights of step platform to 20 centimetre.